Evolution of speech-specific cognitive adaptations - de Boer, Bart (Frontiers in Psychology, 2015)
This paper briefly reviews theoretical results that shed light on what kind of cognitive adaptations we can expect to have evolved for (combinatorial) speech and then reviews concrete empirical work investigating adaptations for combinatorial speech. The paper argues that an evolutionary perspective is natural when investigating cognitive adaptations related to speech and language. This is because properties of language are determined through complex interaction between biologically evolved cognitive mechanisms (possibly adapted to language) and cultural (evolutionary) processes. It turns out that there is as yet no strong direct evidence for cognitive traits that have undergone selection related to speech in general or combinatorial structure in particular, but there is indirect evidence that indicates selection. However, the traits that may have undergone selection are expected to be continuously variable ones, rather than the discrete ones that linguists have focused on traditionally.